Dietary Interventions with Bletilla striata Polysaccharides and/or Composite Polysaccharides Remodel Liver Lipid Profiles and Ameliorate Gut Metabolic Disturbances in High-Fat Diet-Induced Obese Mice - Peiting Zhang; Jinjin Dong; Jiamin Lu; Zijian Cai; Bingde Zhou; Qian Zhang; Chenglin Zhu; Luca Laghi (Foods)
The global obesity epidemic and associated metabolic disorders present urgent public health challenges. This study employed a multi-omics approach (lipidomics, metabolomics, and gut microbiome analysis) to investigate how Bletilla striata polysaccharides (BSPs) and composite polysaccharides modulate liver lipid metabolism and gut microbiota in high-fat diet (HFD)-induced obese mice. HFD elevated hepatic phosphatidylcholines, cholesteryl esters (CEs), and acylcarnitines (CARs), alongside increased cecal choline and trimethylamine. BSP interventions reduced hepatic CEs, free fatty acids (FAs), CARs, and cecal sarcosine while restoring gut microbial diversity. Notably, BSP enriched beneficial genera, including Jeotgalicoccus and Atopostipes, and the network analysis revealed negative correlations between these genera and hepatic triglycerides (TGs), implicating the gut–liver axis in lipid metabolism regulation. These findings elucidate the anti-obesity mechanisms of polysaccharides through gut microbiota remodeling and cross-tissue metabolic interactions, providing a foundation for leveraging plant polysaccharides in developing safer, effective obesity therapies.